Abundance of Selected Fish Species in Relation to Temperature and Salinity Patterns in the Sagavanirktok Delta, Alaska, Following Construction of the Endicott Causeway - Griffiths, William B.; Fechhelm, Robert G.; Gallaway, Benny J.; Martin, Larry R.; Wilson, William J. (ARCTIC, 1998)
Hydrography data from 1985 to 1993 in the vicinity of the Endicott Causeway near Prudhoe Bay, Alaska, were analyzed to determine if the trend in yearly post-causeway construction temperature and salinity was toward colder and more saline conditions. No significant (P<=0.05) relationship was found for temperature; however, salinity levels significantly decreased with time following construction. Intra-year variations in hydrographic conditions appeared to be due to coast-wide meteorological and oceanographic events rather than causeway-induced. We analyzed abundance indices, as log e, transformed catch-per-unit-effort (CPUE), of four marine species (arctic cod, Boreogadus saida; fourhorn sculpin, Myoxocephalus quadricornis; arctic flounder, Pleuronectes glacialis; saffron cod, Eleginus gracilis); two freshwater species (round whitefish, Prosopium cylindraceum; arctic grayling, Thymallus arcticus); and the anadromous rainbow smelt, Osmerus mordax, to determine whether there were increases in the abundance of marine species and declines in anadromous and freshwater species. We developed the "best-fit" regression models, based on the criterion of maximized regression F-ratio (i.e., minimized regression p-values), using year, temperature, salinity, and all possible interactions. Results suggested that all species exhibited changes in abundance levels over the period of record. In particular, arctic flounder and rainbow smelt both showed sharp increases in abundance five years after construction. For all species, the observed changes in abundance levels appears to be due to naturally occurring events in the species life history or changes in coast-wide meteorological conditions rather than to causeway-induced alterations in local hydrographic conditions. On a analysé les données hydrographiques obtenues de 1985 à 1993 dans le voisinage immédiat du pont-jetée Endicott situé près de Prudhoe Bay en Alaska, en vue de déterminer si, après la construction du pont, la température annuelle avait tendance à être plus ...